The Impact of Electrical Vehicles on Sustainability: Jordan as a Case Study - Shatnawi Malak M. (International Journal of Engineering and Management Sciences, 2019)
The Global concern is moving toward making a revolution in favor of exploitation of renewable energy in order to improve environment conditions, limit emissions and minimizes consumption of non-renewable resources within the planet. In this context, it is necessary to focus on the transport sector as it contributes of at least 30% of the total primary energy consumption. Therefore, a set of rules must be developed to maintain economic, environmental and social sustainability to address the problems so as not to increase their severity and these cannot be done unless there are joint measures and regulations from governments, companies, manufacturers and users. Unfortunately, the Jordanian transport system mostly depend on the individual transport which supported by cars, and that because of the weak role played by the public transport sector, especially at the capital, Amman. Buying hybrid cars (internal combustion engine + electric motor) and Electrical Vehicles (EV), in the past few years in Jordan is increasing, which is compatible with the global trend to use Electrical Vehicles (EV) instead of Internal Combustion Engine vehicles (ICE) powered by fossil fuels, this issue will have a direct and indirect impact on gas stations companies, also it will have direct impact on labor sector and the current car industry since electric charging stations as well as EV manufacturing is not labor intensive. The main purpose of the study is to show how much it is necessary now to start theoretical assumptions through studying the expected annual increase in passenger cars and its impact on sustainability and predicting the future fuel consumption and emissions and compare them with the base situation.